Analisis Kesalahan Peserta Didik dalam Menyelesaikan Soal Model PISA pada Konten Change and Relationship - Mayana; Thamrin Tayeb; Suharti (Department of Mathematics Education, 2024)
This study was motivated by Indonesia's low ranking in PISA results from 2000 to 2022. This shows that many students still experience errors in solving PISA questions. This study aims to describe the percentage of students' errors, the types of students' errors and the factors that cause students' errors in class VIII SMPN 40 Makassar in solving PISA questions on the content of change and relationship. This research method uses descriptive research with a quantitative approach. Data collection techniques were carried out using tests, structured interviews, and documentation. The sample in this study were students of grade VIII of SMPN 40 Makassar, totaling 189 students. The results showed that the percentage of errors made by students in solving PISA questions on the content of change and relationship were: (1) errors in understanding the problem of 69.68% in the “very high” category, (2) planning errors of 65.93% in the “very high” category, (3) completion errors of 71.27% in the “very high” category, and (4) rechecking errors of 85.93% in the “very high” category. The factors of students experiencing errors in understanding the problem are because they interpret it incorrectly, are confused about what to write and are not accustomed to writing known and questionable things in answering problems. The planning error factor is due to not understanding the concept so that it is wrong in choosing the formula and not being able to know the steps in solving the problem. The error factor in solving is due to not mastering mathematical operations so that it is wrong in process skills when doing calculations. The error factor in checking back is due to previous mistakes and the absence of re-evaluation.